Software Product Lines: Going Beyond 14th International Conference, SPLC 2010, Jeju Island, South Korea, September 13-17, 2010. Proceedings - Bosch, Jan; Lee, Jaejoon (Programming and Software Engineering, 2010)
This volume constitutes the refereed proceedings of the 14th International Software Product Line Conference, SPLC 2010, held on Jeju Island, South Korea, in September 2010.